Pendampingan Penyusunan Laporan Keuangan Sesuai Standar Akuntansi Keuangan pada UMKM Toko Bunga - Bavani, Melinda; Tjahjono, Yosephine Mevia; Airell, Vernando; Brilliant, Nicholas; Malelak, Mariana Ing (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are one of the main pillars supporting the Indonesian economy. Over time, the number of MSMEs in Indonesia has shown significant growth. However, unfortunately, this growth has not been accompanied by development in the financial aspect. This is evidenced by the numerous MSMEs that still face challenges in managing and preparing financial statements in accordance with Financial Accounting Standards. One of the MSMEs facing obstacles is Vialin Florist, an MSME engaged in floral arrangements and has been operating since 2022 through a digital platform. This research aims to assist Vialin Florist in preparing financial statements in accordance with the Financial Accounting Standards for Micro, Small, and Medium-sized Entities (SAK-EMKM). The method applied is mentoring by providing understanding and guidance to partners in preparing financial statements using Microsoft Excel. The results show that mentoring activities can increase the knowledge and abilities of Vialin Florist’s owners in preparing financial statements more accurately and in accordance with standards. The improvement in the quality of financial statements is expected to positively contribute to the decision-making process undertaken by MSMEs.